Evaluating Preceptee’s Learning Achievements During the Covid-19 Pandemic - Rumbo, Helmi; Mbaloto, Freny Ravika; Mauruh, Chely Veronica; Metungku, Fanny; Sondakh, Julianti Reygina; Ambabunga, Sriwanti (KnE Life Sciences, 2021)
Since the beginning of the Covid-19 pandemic, higher education institutions in Indonesia have had to revise their learning management systems to ensure they can be accessed from anywhere and anytime by students and lecturers. This study aims to evaluate whether there is a difference in learning achievement by Nursing Students in the professional stage (Ners Preceptee) when comparing offline learning programs with online programs. The independent variable is learning method; the dependent variable is learning achievement. A cross-sectional study design was conducted through a secondary data. This study used two different groups, in which preceptees’ score’ within offline learning programs and online learning programs were compared in June 2020. A total of 52 Ners Preceptee scores were analyzed by using Mann-Whitney U test. The result revealed that significant differences exists in median Learning Achievement scores between the online group and offline group (p = 0.002). It can be concluded that Learning Management Systems including supporting facilities can have an impact on student learning outcomes. Keywords: Learning, Method, Covid-19, Ners, Profession.